2018
DOI: 10.3390/lubricants6040092
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Surface Texturing on Dry Gross Fretting

Abstract: The effect of steel disc surface texturing on dry gross fretting in a ball-on-disc configuration was studied. Dimples were created with abrasive jet machining. The tribological performance of sliding pairs, steel–steel and steel–ceramics, was experimentally studied. The character of surface texturing effect was related to the dominant wear type. During steel–steel contact, the presence of dimples on disc surfaces could lead to increases in wear and friction. However, the escape of wear debris into dimples coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…Experimental researches [6], [7], [8], [10], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46], [47] 34 *Total number of references in each group of research conditions differs from 40 because in some references more than one research condition of the same group is investigated. In addition, references with simulations usually do not have the surface texturing technique defined…”
Section: Methodology Of Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental researches [6], [7], [8], [10], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43], [44], [45], [46], [47] 34 *Total number of references in each group of research conditions differs from 40 because in some references more than one research condition of the same group is investigated. In addition, references with simulations usually do not have the surface texturing technique defined…”
Section: Methodology Of Researchmentioning
confidence: 99%
“…The vibrorolling principle is based on the transfer of hard indenter shape (pattering) on the work piece surface, by plastic deformation. Other techniques include lithography and anisotropic etching [18], photochemical etching (masking by photolithography followed by chemical etching) [19], photolithography combined with electrolytic etching process [20], focused ion beam milling [21] and abrasive jet machining [22], etc. The frequency of laser surface texturing usage compared to others techniques is presented in Table 1.…”
Section: Surface Texturing Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Kümmel et al, 15 investigated the tribological behavior of Ti6Al4V in the case of the grease‐lubricated sliding condition using a linear laser texture with attention on laser‐induced melt bulges and found that untextured samples showed high adhesive wear and a higher COF through the running‐in duration. Lenart et al, 16 studied the response of texturing on 42CrMo4 using ball on flat configuration under dry gross fretting. The impact of surface texturing on friction and wear properties under gross fretting circumstances depends on the sliding materials’ ability to form adhesive junctions.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of [41] investigated the influence of the surface texture of steel discs contacting ceramic balls on the tribological performance of the sliding assembly in a dry gross sliding fretting regime and found that the results were better for lower disc roughness heights. The influence of disc surface texturing on dry gross sliding fretting of a ball-on-disc assembly was investigated [42]. The effect of surface texturing depended on the dominant wear type (adhesion or abrasion).…”
Section: Introductionmentioning
confidence: 99%